P510Obtention and characterization of acellular myocardial scaffold for cardiac tissue engineering. (15th July 2014) - Perea Gil, I; Uriarte, JJ; Prat-Vidal, C; Galvez-Monton, C; Roura, S; Llucia-Valldeperas, A; Soler-Botija, C; Farre, R; Navajas, D; Bayes-Genis, A
Abstract: Purpose: Cardiac tissue engineering emerges as a promising alternative to current therapies addressed to myocardial infarction. In this context, we aimed to obtain and characterize myocardial bioprosthesis based on a decellularized matrix capable of being engrafted in damaged myocardium. Methods: Myocardial blocks (3x3 cm), differentiating epicardial, mesocardial and endocardial regions, were obtained from cadaveric porcine hearts (n=5) and decellularized using two different protocols: Protocol 1 (P1) combines chemical (ionic and non-ionic detergents), enzymatic (DNase) and physical (agitation) treatments, and Protocol 2 (P2) is based on a combination of chemical (non-ionic detergent, acid, hypotonic and hypertonic solutions), enzymatic (trypsin) and physical (agitation) procedures. Decellularization level was assessed histologically (Masson's Trichrome stain and immunohistochemistry) and molecularly (DNA quantification). The resulting acellular structure was examined by scanning electron microscopy. Extracellular matrix components were analyzed by immunohistochemistry and local matrix stiffness was determined by measuring the Young's modulus with atomic force microscopy. Biodegradability of decellularized matrices was evaluated in vitro with collagenase treatment. Results: Total absence of cells after decellularization was confirmed by Trichrome staining and immunohistochemistry. DNA content was significantly reduced in both protocols (P1: 86.0±1.7%, P2: 96.3±1.1%, compared to native tissue; p<0.001), with significant differences between them (p<0.001). Remarkably, integrity of matrix filaments was preserved due the presence of type-I collagen and elastin. Mechanical testing revealed no significant changes in stiffness of decellularized matrices when compared to native tissue (Native: 27.5±4.9, P1: 33.0±10.7, P2: 40.0±7.1 kPa; p=0.55). The biodegradability assay also confirmed complete degradation of matrices without differences among protocols (Weight loss: P1: 90.1±5.4%, P2: 93.8±5.1%; p=0.19). Finally, non-significant differences were found in epicardial, mesocardial and endocardial decellularized blocks in terms of cells removal, structural, proteical or mechanical characterization. Conclusions: Acellular myocardial matrices were successfully obtained by both decellularization protocols, preserving major structural components so as mechanical and biodegradability properties.Furthermore, trypsin-based protocol (P2) yielded less DNA residues which could contribute to prevent rejection.